A note on the minimum reduced reciprocal Randic index of n-vertex unicyclic graphs - Ali, Akbar; Bhatti, Akhlaq A. (Kuwait Journal of Science, 2017)
Recent studies show that the reduced reciprocal Randi? (RRR) index possesses the second-best correlating ability amongthe several well known topological indices. Hence, it is meaningful to study the mathematical properties of the (RRR)index, especially bounds and characterization of the extremal elements for renowned graph families. In the present note, the unicyclic graph having minimum (RRR)index is characterized among the class of all -vertex unicyclic graphs.